The Cerebral Hercules and the Bankruptcy Hydra: How Judge Schermer Slayed a Multi-Headed Monster While Deep in the Heart of Texas (and What Any of This Lone Star State-Grecian Hero Analogy Has to Do with Just a Little Bit of Yiddish) - Charles E. Rendlen III; Abigail B. Willie (Washington University Journal of Law & Policy, 2017)
This Article revisits Judge Barry Schermer’s approaches to complex matters as a bankruptcy mediator. In Part I, Judge Rendlen explains Judge Schermer’s jurisprudence while mediating the particularly complicated Chapter 11 bankruptcy case, In re U.S. Fidelis, Inc., which helped attain a decision that prevented the estate’s assets drying up in litigation and protect hundreds of thousands of victims of deceptive practices by U.S. Fidelis. In Part II, Willie attests to Judge Schermer’s humanity, which allows him to focus on important underlying matters rather than simply attaining a resolution.
Keywords: Chapter 11 Bankruptcy; Mediation; WARN Act; Corporate Bankruptcy; Judge Schermer; Judicial Mediation